Enhanced vector control of doubly-fed induction generator based wind turbines to comply with the Australian Grid Code requirements - Mohseni, Mansour; Islam, Syed (Engineers Australia, 2011)
Recent regulatory requirements outlined in the Australian Grid Code dictates fault ride-through and voltage support requirements for wind energy conversion systems. This paper introduces an enhanced vector control scheme for doubly-fed induction generator (DFIG) based wind turbines to comply with these requirements. A unified three-phase signal processor (UTSP) is implemented to readily extract the synchronisation signal from the three-phase grid voltage. The proposed UTSP is also used for the on-line calculation of the grid voltage amplitude, which is needed to provide the reactive power support according to the Australian regulations. The standard proportional-integral current regulators in the rotor-side and grid-side converters are replaced with vector-based hysteresis current regulators to increase the voltage sag/swell ride-through capacity of DFIG. The main advantages of the proposed current regulator are its very fast transient response and simple control structure. Simulation results show the effectiveness of the proposed vector controller to comply with the Australian Grid Code requirements under various grid disturbances.